Skeletal muscle lactate overproduction during metformin intoxication: An animal study with reverse microdialysis. (25th July 2016) - Protti, Alessandro; Properzi, Paolo; Magnoni, Sandra; Santini, Alessandro; Langer, Thomas; Guenzani, Silvia; Ferrero, Stefano; Bassani, Giulia; Stocchetti, Nino; Gattinoni, Luciano
Highlights: Lactic acidosis is a life-threatening complication of metformin use. It may be due to excessive inhibition of lactate clearance through liver gluconeogenesis. We infused high dose of metformin in gluteus muscle of pigs with reverse microdialysis. Dialysate (interstitial) lactate level and lactate-to-pyruvate ratio rose over time. Lactate overproduction can contribute to metformin-induced lactic acidosis. Abstract: Lactic acidosis during metformin intoxication is classically mainly attributed to diminished lactate clearance through liver gluconeogenesis. Here we studied 6 healthy, sedated and mechanically ventilated pigs to clarify whether high dose of metformin also increases skeletal muscle lactate production . Each animal had two microdialysis catheters inserted in gluteus muscles, one per side. One catheter was infused with saline (control) while the other one was infused with metformin diluted in saline (1 M), both at a rate of 0.3 μl/min. Dialysate lactate concentration and lactate-to-pyruvate ratio, a marker of the balance between anaerobic glycolysis and aerobic (mitochondrial) metabolism, were measured every 3 h, for 12 h. Continuous infusion of metformin caused a progressive rise in dialysate lactate level (p = 0.007) and lactate-to-pyruvate ratio (p < 0.001) compared to that of saline, as for mitochondrial "poisoning". These findings suggest that skeletal muscle lactate overproduction contributes to the development of metformin-induced lactic acidosis.